2019
DOI: 10.1101/776310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic rejuvenation of the hippocampus by environmental enrichment

Abstract: 10The decline of brain function during aging is associated with epigenetic changes, including DNA 11 methylation. Lifestyle interventions can improve brain function during aging, but their influence 12 on age-related epigenetic changes is unknown. Using genome-wide DNA methylation sequencing, 13 we here show that environmental enrichment counteracted age-related DNA methylation changes 14 in the hippocampal dentate gyrus of mice. Specifically, environmental enrichment prevented the 15 aging-induced CpG hypomet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 77 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…CpH methylation changes have also been reported at 750 cytosines, primarily occurring in introns, in the hippocampi of mice housed in EE (Zocher et al, 2021). While DNAm at introns has the potential to influence transcription, differential CpH methylation was also shown to be depleted at promoters, CpG islands, and CpG shores in this study, making it difficult to draw any definitive conclusions about potential gene regulatory impacts (Zocher et al, 2021). Neuronal CpH methylation has been suggested to be more sensitive to environmental stimuli than neuronal CpG methylation due to its sparsity and replication independence (Fuso and Lucarelli, 2019).…”
Section: Influence Of Genetics and Environment On Non-cpg Methylationmentioning
confidence: 88%
See 3 more Smart Citations
“…CpH methylation changes have also been reported at 750 cytosines, primarily occurring in introns, in the hippocampi of mice housed in EE (Zocher et al, 2021). While DNAm at introns has the potential to influence transcription, differential CpH methylation was also shown to be depleted at promoters, CpG islands, and CpG shores in this study, making it difficult to draw any definitive conclusions about potential gene regulatory impacts (Zocher et al, 2021). Neuronal CpH methylation has been suggested to be more sensitive to environmental stimuli than neuronal CpG methylation due to its sparsity and replication independence (Fuso and Lucarelli, 2019).…”
Section: Influence Of Genetics and Environment On Non-cpg Methylationmentioning
confidence: 88%
“…These studies showed that environmental enrichment can alter hippocampal DNAm and DNAhm, and prevent some SNCA-induced alterations in gene expression (Irier et al, 2014;Wassouf et al, 2018;Zhang et al, 2018;Zocher et al, 2021). Intriguingly, EE was shown to reduce age-related epigenetic drift at the level of DNAm in the hippocampus, and to alter histone modifications, chromatin accessibility, DNAm, and gene expression in the cortex in mice (Espeso-Gil et al, 2021;Zocher et al, 2021). These studies support a potential role of DNAm as a mediator of the impacts of behavior and lifestyle-related factors on PD risk.…”
Section: Physical Activity Enriched Environment and Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…That elevated PV + neuron L1 activity in adult DG was here moderately attenuated, rather than increased, by ENR housing, and not affected by voluntary exercise, was therefore unexpected. Environmental enrichment may counter physiological stress upon PV + neurons [67][68][69] , and could enhance L1 repression 70 . As shown in other biological contexts 1,3,10,21 , L1 activation in PV + neurons illustrates how retrotransposons may be incorporated into transcription factor programs guiding cell fate and mature function, potentially in an experience-dependent manner.…”
mentioning
confidence: 99%